Media, culture and society in Malaysia - Yeoh, Seng Guan (Routledge Malaysian studies series, 2010)
Presents a comprehensive analysis of the uses of media and communication technologies by different social actors in Malaysia. Drawing upon case studies - from films to political advertising - this book provides insights into the ways in which different media forms have negotiated with the dominant cultural representations of Malaysian society.